Positive electrode material, positive electrode plate and sodium ion battery
By introducing sulfur-containing additives into the positive electrode material of the sodium ion battery, it is reduced to polysulfur ions during the charging and discharging process, reacts with the organic solvent in the electrolyte, and introduces sulfur elements into the electrolyte to generate a stable SEI film and improves the sodium ion transfer rate at the positive electrode interface, solving the unstable rate performance and cyclic performance problems of sodium ion battery, achieving efficient cyclic performance improvement and economic cost reduction.
Patent Information
- Application Number
- CN202411969176.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Due to the large ion radius of Na+, sodium ion batteries have slow diffusion kinetics and significant changes in the electrode material volume, which in turn leads to unstable rate performance and cyclic performance. The existing methods design stable inorganic rich interfaces through electrolytes have higher economic costs.
The sulfur-containing additive is introduced into the positive electrode material, so that it is reduced to polysulfur ions during the charge and discharge process, reacts with the organic solvent in the electrolyte, and introduces sulfur elements into the electrolyte to form a stable SEI film and improves the sodium ion transfer rate at the positive electrode interface.
By introducing sulfur-containing additives, a stable SEI film is generated and the sodium ion transfer rate is improved at the positive electrode interface, which significantly improves the circulation performance of the sodium ion battery and reduces economic costs.
Smart Images

Figure CN119725543A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have attracted extensive attention due to their abundant sodium resources and similar working mechanism to lithium-ion batteries. + The relatively large ionic radius leads to slow diffusion kinetics and significant volume changes of electrode materials, which in turn lead to unstable rate performance and cycle performance of sodium-ion batteries. + The diffusion of the positive electrode and the stability of the electrode material play a key role. However, due to the high solubility of key components of the interface (such as NaF) in the electrolyte, the interface of the sodium ion battery is unstable. Therefore, it is urgent to explore an effective method to simultaneously construct a stable interface layer on the surface of the positive and negative electrodes to improve the electrochemical performance of sodium ion batteries.
[0003] Currently, electrolyte design strategies are often used to construct stable inorganic-rich interfaces with good Na + Sulfur-containing interfaces with improved transport rate and stability are considered to be a promising strategy for building high-performance sodium-ion batteries. Introducing sulfur-containing component additives into the electrolyte is a very direct and effective approach, but the economic cost is high.
[0004] Therefore, it is desirable to provide a more economical method for introducing sulfur components into the positive / negative electrode interface of sodium ion batteries. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a positive electrode material, a positive electrode plate and a sodium ion battery. The present invention introduces a sulfur-containing additive into the positive electrode material so that it is reduced to polysulfide ions during the charge and discharge process, and the polysulfide ions react with the organic solvent in the electrolyte, thereby introducing sulfur into the electrolyte as an additive. On the one hand, the additive can generate a stable SEI film with sulfur-containing components at the negative electrode interface, and on the other hand, it can effectively improve the sodium ion transmission rate at the positive electrode interface, thereby effectively improving the cycle performance of the sodium ion battery.
[0006] In a first aspect, the present invention provides a positive electrode material, which includes a positive electrode active material, a first binder, a first conductive agent and a sulfur-containing additive.
[0007] The present invention introduces a sulfur-containing additive into the positive electrode material so that the additive is reduced to polysulfide ions during the charge and discharge process. The polysulfide ions react with the organic solvent in the electrolyte, thereby introducing sulfur into the electrolyte as an additive. On the one hand, the additive can generate a stable SEI film with sulfur-containing components at the negative electrode interface, and on the other hand, it can effectively improve the sodium ion transmission rate at the positive electrode interface, thereby effectively improving the cycle performance of the sodium ion battery. Specifically:
[0008] A sulfur-containing additive is introduced into the positive electrode material provided by the present invention, and the sulfur-containing additive is reduced to polysulfide ions during the charge and discharge process. The polysulfide ions react with the ester organic solvent in the electrolyte. The carbon connected to oxygen in the linear and / or cyclic carbonate solvent has electrophilicity, and the polysulfide ions have nucleophilicity. For carbonate, no matter the polysulfide ions attack the carbon atom of the carbon-oxygen double bond or the carbon atom of the carbon-oxygen single bond to generate polythiocarbonate or polysulfide-substituted alkoxide, the sulfur element can be introduced into the electrolyte as an additive. On the one hand, the sulfur-containing product can be reduced at the negative electrode to generate a stable SEI film containing sodium sulfide components and other organic / inorganic salt components containing sulfur elements; on the other hand, the strong interaction between the sulfur-containing product and the organic solvent can accelerate the desolvation process of sodium ions before being embedded in the positive electrode material, thereby achieving the purpose of improving the sodium ion transport at the positive electrode interface. At the same time, it may also be oxidized to sulfate, sulfonate, carbonate and other components to varying degrees on the positive electrode side, thereby effectively improving the cycle performance of the sodium ion battery.
[0009] As a preferred technical solution of the present invention, the sulfur-containing additive includes sulfur element and / or sulfur-carbon material, and the sulfur element can be sublimated sulfur powder.
[0010] As a preferred technical solution of the present invention, based on the total mass of the positive electrode material as 100%, the content of the sulfur-containing additive is 0.02-3%, for example, 0.02%, 0.05%, 0.08%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc.
[0011] When the content of the sulfur-containing additive is within the above range, the content of the sulfur-containing additive (polythiocarbonate or polysulfide-substituted alcohol salt) finally introduced into the electrolyte can be within a suitable range, thereby effectively improving the rate performance and cycle performance of the sodium ion battery. Too low or too high a content of the sulfur-containing additive will lead to poor performance.
[0012] As a preferred technical solution of the present invention, the positive electrode active material includes any one or more of transition metal layered oxides, polyanion positive electrode materials and Prussian blue positive electrode materials.
[0013] As a preferred technical solution of the present invention, the first binder includes any one or more of PVDF, PAN, PMMA, PBA and PA.
[0014] As a preferred technical solution of the present invention, the first conductive agent includes any one or more of conductive carbon black, graphene, carbon nanotubes and carbon fibers.
[0015] As a preferred technical solution of the present invention, based on the total mass of the positive electrode material being 100%, the content of the positive electrode active material is 91.5-97%, for example, 91.5%, 92%, 94%, 96%, 97%, etc.
[0016] As a preferred technical solution of the present invention, based on the total mass of the positive electrode material as 100%, the content of the first binder is 2.5-7%, for example, 2.5%, 3%, 5%, 6%, 7%, etc.
[0017] As a preferred technical solution of the present invention, based on the total mass of the positive electrode material as 100%, the content of the first conductive agent is 0.5-2.3%, for example, 0.5%, 1%, 1.5%, 2%, 2.3%, etc.
[0018] As a preferred technical solution of the present invention, the positive electrode material also includes a sodium supplement.
[0019] As a preferred technical solution of the present invention, the sodium supplement includes any one or more of sodium oxide, sodium sulfide and sodium oxalate.
[0020] As a preferred technical solution of the present invention, based on the total mass of the positive electrode material as 100%, the content of the sodium supplement is 0.1-30%, for example, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc.
[0021] In a second aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material described in the first aspect.
[0022] In a third aspect, the present invention provides a sodium ion battery, comprising the positive electrode plate and the negative electrode plate described in the second aspect, an electrolyte and a separator.
[0023] As a preferred technical solution of the present invention, the negative electrode plate includes a negative electrode material, and the negative electrode material includes a negative electrode active material, a second binder and a second conductive agent.
[0024] As a preferred technical solution of the present invention, the negative electrode active material includes any one or more of carbon materials, metal materials, and metal compounds, preferably hard carbon materials.
[0025] As a preferred technical solution of the present invention, the second binder includes any one or more of CMC, PAA, SBR, PAN and PVA.
[0026] As a preferred technical solution of the present invention, the second conductive agent includes any one or more of conductive carbon black, graphene, carbon nanotubes and carbon fibers.
[0027] As a preferred technical solution of the present invention, the electrolyte includes sodium salt, organic solvent and ester additives.
[0028] As a preferred technical solution of the present invention, the sodium salt includes any one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate and sodium bis(fluorosulfonyl)imide.
[0029] As a preferred technical solution of the present invention, the organic solvent includes any one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC).
[0030] As a preferred technical solution of the present invention, the content of the ester solvent in the organic solvent is greater than 5wt%.
[0031] As a preferred technical solution of the present invention, the ester additive includes fluoroethylene carbonate (FEC) and / or vinylene carbonate (VC). The electrolyte provided by the present invention can effectively improve the electrochemical performance of the sodium ion battery without adding an additive containing a sulfur component.
[0032] As a preferred technical solution of the present invention, the diaphragm includes a PE film, a PP film, a PP-PE-PP film, a nanofiber diaphragm and a glass fiber diaphragm.
[0033] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:
[0034] The present invention introduces a sulfur-containing additive into the positive electrode material so that the additive is reduced to polysulfide ions during the charge and discharge process. The polysulfide ions react with an organic solvent in the electrolyte, thereby introducing sulfur into the electrolyte as an additive. On the one hand, the additive can generate a stable SEI film with sulfur-containing components at the negative electrode interface, and on the other hand, it can effectively improve the sodium ion transmission rate at the positive electrode interface, thereby effectively improving the cycle performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0037] Figure 1 The graphs are the cycle performance of sodium ion batteries assembled with positive electrode sheets prepared in different embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0038] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0040] Example 1
[0041] This embodiment provides a positive electrode sheet and a preparation method thereof, the preparation method comprising the following steps:
[0042] Take 4800g of sodium vanadium phosphate, 48g of sublimated sulfur powder, 153g of polyvinylidene fluoride, 51g of conductive carbon black, and 30g of carbon nanotubes, and use N-methylpyrrolidone as solvent for wet homogenization. The slurry is evenly dispersed, with a viscosity of 5000-6000mPa·s. Coat it on both sides of the carbon-coated aluminum foil, and the double-sided surface density is 161.6g / m 2 , roller compaction, compaction density 1.56kg / m 3 , die cutting, baking, single-sided capacity density 8.45Ah / m 2 .
[0043] Example 2
[0044] This embodiment provides a positive electrode sheet and a preparation method thereof. The preparation method is the same as that of Embodiment 1. The difference from Embodiment 1 is that the sublimated sulfur powder in this embodiment is 24g and the double-sided surface density is 160.8g / m 2 .
[0045] Example 3
[0046] This embodiment provides a positive electrode sheet and a preparation method thereof. The preparation method is the same as that of Embodiment 1. The difference from Embodiment 1 is that the sublimated sulfur powder in this embodiment is 9.6 g, and the double-sided surface density is 160.3 g / m2 .
[0047] Example 4
[0048] This embodiment provides a positive electrode plate and a preparation method thereof. The preparation method is the same as that of Example 3. The difference from Example 3 is that the sublimated sulfur powder in this embodiment is 4.8 g.
[0049] Example 5
[0050] This embodiment provides a positive electrode plate and a preparation method thereof. The preparation method is the same as that of Example 3. The difference from Example 3 is that the sublimated sulfur powder in this embodiment is 2.4 g.
[0051] Example 6
[0052] This embodiment provides a positive electrode plate and a preparation method thereof. The preparation method is the same as that of Example 3. The difference from Example 3 is that the sublimated sulfur powder in this embodiment is 1.2 g.
[0053] Example 7
[0054] This embodiment provides a positive electrode sheet and a preparation method thereof. The preparation method is the same as that of Embodiment 1. The difference from Embodiment 1 is that the sublimated sulfur powder in this embodiment is 155.7 g, and the double-sided surface density is 161.6 g / m 2 .
[0055] Example 8
[0056] This embodiment provides a positive electrode sheet and a preparation method thereof, the preparation method comprising the following steps:
[0057] Take 4621g of sodium vanadium phosphate, 179g of sulfur-carbon material LMC / S composite material (S content 26.91%), 153g of polyvinylidene fluoride, 51g of conductive carbon black, and 30g of carbon nanotubes, and use N-methylpyrrolidone as solvent for wet homogenization. The slurry is evenly dispersed and has a viscosity of 5000-6000mPa·s. It is coated on both sides of carbon-coated aluminum foil with a double-sided surface density of 161.6g / m 2 , roller compaction, compaction density 1.56kg / m 3 , die cutting, baking, single-sided capacity density 8.45Ah / m 2 .
[0058] Example 9
[0059] This embodiment provides a positive electrode plate and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that 4.8 g of sodium oxalate sodium supplement is further added to the positive electrode slurry in this embodiment.
[0060] Example 10
[0061] This embodiment provides a positive electrode sheet and a preparation method thereof. The preparation method is the same as that of Embodiment 1. The difference from Embodiment 1 is that the sublimated sulfur powder in this embodiment is 265g, and the double-sided surface density is 161.1g / m 2 .
[0062] Comparative Example 1
[0063] This comparative example provides a positive electrode sheet and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that no sublimated sulfur powder is added in this comparative example, and the double-sided surface density is 160g / m 2 .
[0064] Application Examples
[0065] The positive electrode sheets prepared in the embodiment and the comparative example were assembled into sodium ion batteries respectively:
[0066] (1) Negative electrode sheet: 4800 g of hard carbon, 100 g of polyvinylidene fluoride, and 100 g of conductive carbon black were wet homogenized using N-methylpyrrolidone as solvent. The slurry was evenly dispersed and had a viscosity of 2000-4000 mPa·s. The slurry was coated on both sides of the carbon-coated aluminum foil with a double-sided surface density of 62 g / m 2 , roller compaction, compaction density 0.83kg / m 3 , die cutting, baking, single-sided capacity density 9.22Ah / m 2 .
[0067] (2) Electrolyte: A 1 mol / L NaPF6 solution was prepared according to the volume of the solvent. The solvent was a mixed solvent with a volume ratio of EC / PC / EMC / DEC = 1:1:2:2. The mass of this solution was taken as 100%. Different mass fractions of additives (FEC, fluoroethylene carbonate; PS, 1,3-propane sultone) were additionally added. The specific amounts of the additives are shown in Table 1:
[0068] Table 1
[0069]
[0070]
[0071] (3) Diaphragm: PE base film + alumina coating (9 μm + 3 μm).
[0072] (4) The battery cells are stacked, the pole ears are welded, the battery cells are placed in the shell, and the liquid is injected in the dehumidification room. The designed capacity of the battery cells is 1Ah, and the battery injection coefficient is 12g / Ah.
[0073] After the battery cell is filled with liquid, the battery cell is vacuum packaged and placed at 45℃ for 48 hours, and then placed at room temperature for 12 hours. Pressurized and heated, the battery cell is subjected to a constant pressure of 0.8MPa and a temperature of 35℃, and is charged to 3.65V at a constant current of 0.5A, and then discharged to 1V at a constant current of 0.5A, and then placed at 25℃ for 30 minutes, and then charged at a constant current of 0.5A for 7 hours, and the formation is completed. The electrochemical performance is tested after final sealing.
[0074] Performance Testing
[0075] Cycle performance test: Place the sodium ion battery assembled in the application example in a constant temperature chamber, and control the temperature of the constant temperature chamber between room temperature 25±5℃, and let it stand for 30 minutes to allow the sodium ion battery to reach room temperature. Charge the sodium ion battery that has reached constant temperature with a constant current of 1C to 3.65V, then charge it with a constant voltage until the current drops to 0.05C, and then discharge it with a constant current of 1C to 2V. Repeat this cycle, record the discharge capacity of the first cycle and the discharge capacity of the last cycle, and calculate the capacity retention rate according to the following formula:
[0076] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity / first cycle discharge capacity) × 100%.
[0077] Test results such as Figure 1 As shown in Table 2, Figure 1 The cycle performance diagram of the sodium ion battery assembled with the positive electrode sheets prepared in different embodiments and comparative examples;
[0078] The results in Table 2 are as follows:
[0079] Table 2
[0080]
[0081] It can be found from Table 2 that the sodium ion battery assembled with the positive electrode sheet prepared using the positive electrode material provided by the present invention has a more excellent cycle performance.
[0082] From the comparison between Application Example 1 and Comparative Application Example 1, it can be found that the introduction of sulfur-containing additives into the positive electrode material in the present invention can effectively improve the cycle performance of the sodium ion battery.
[0083] From the comparison between Application Example 1 and Comparative Application Examples 2-4, it can be found that the introduction of the sulfur-containing additive into the positive electrode material of the present invention has a better effect on improving the cycle performance of the sodium ion battery than directly adding the sulfur-containing additive into the electrolyte.
[0084] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0085] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a positive electrode active material, a first binder, a first conductive agent and a sulfur-containing additive.
2. The positive electrode material according to claim 1, characterized in that The sulfur-containing additive includes sulfur and / or sulfur-carbon material; And / or, based on the total mass of the positive electrode material being 100%, the content of the sulfur-containing additive is 0.02-3%.
3. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode active material includes any one or more of transition metal layered oxides, polyanion positive electrode materials and Prussian blue positive electrode materials; And / or, the first binder includes any one or more of PVDF, PAN, PMMA, PBA and PA; And / or, the first conductive agent includes any one or more of conductive carbon black, graphene, carbon nanotubes and carbon fibers.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that Based on the total mass of the positive electrode material being 100%, the content of the positive electrode active material is 91.5-97%; And / or, based on the total mass of the positive electrode material being 100%, the content of the first binder is 2.5-7%; And / or, based on the total mass of the positive electrode material being 100%, the content of the first conductive agent is 0.5-2.3%.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material also includes a sodium supplement; Preferably, the sodium supplement comprises any one or more of sodium oxide, sodium sulfide and sodium oxalate; Preferably, based on 100% of the total mass of the positive electrode material, the content of the sodium supplement is 0.1-30%.
6. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 5.
7. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet and the negative electrode sheet according to claim 6, an electrolyte and a separator.
8. The sodium ion battery according to claim 7, characterized in that: The negative electrode sheet includes a negative electrode material, and the negative electrode material includes a negative electrode active material, a second binder and a second conductive agent; And / or, the electrolyte comprises a sodium salt, an organic solvent and an ester additive; And / or, the separator includes a PE film, a PP film, a PP-PE-PP film, a nanofiber separator and a glass fiber separator.
9. The sodium ion battery according to claim 8, characterized in that: The sodium salt includes any one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate and sodium bis(fluorosulfonyl)imide; and / or, the organic solvent comprises any one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate; And / or, the ester additive includes fluoroethylene carbonate and / or vinylene carbonate.
10. The sodium ion battery according to claim 8 or 9, characterized in that: The negative electrode active material includes any one or more of a carbon material, a metal material, and a metal compound, preferably a hard carbon material; And / or, the second binder includes any one or more of CMC, PAA, SBR, PAN and PVA; And / or, the second conductive agent includes any one or more of conductive carbon black, graphene, carbon nanotubes and carbon fibers.